The ‘humanised zoo’: decolonizing conservation education through a new narrative - S Gippoliti; C Battisti (Ethics in Science and Environmental Politics, 2023)
Wildlife conservation seems unaffected by decolonization movements that recently led to removing or vandalizing several statues of geographers and colonizers worldwide. Instead, we observe an increased emphasis on total protection of species and habitats that, although strategic in a period of environmental crisis, may have grossly negative impacts on living standards of local indigenous communities. In this regard, we should decolonize society, and specifically conservation, by adding new metaphoric statues to the old ones, preferably of those living side by side with wildlife. In this essay, we suggest that zoos, as popular places where urbanized people meet biodiversity, should change their messages that too often reinforce the subtle colonial ideology pervading international environmentalism and often driven by increasing animal rights activism. For example, a new storytelling ethos in zoos should communicate that, in some sensitive contexts (e.g. most tropical countries), the current over-emphasis on protected areas and military law enforcement is also causing serious human rights violations. We need ‘humanised zoos’, i.e. places where conservation of biodiversity is put in a broader socio-ecological context and a central role for the future of ecosystems is given to local communities, ethnic minorities and ‘wise people’ (i.e. people having local traditional knowledge). Zoos should direct more resources toward community-based conservation; foremost, they should shape urban and ‘Western’ attitudes toward wildlife with a less colonized perspective, including spreading the importance of traditional ecological knowledge in ecosystem management.